Perancangan Obyek Wisata Budaya di Desa Rende Dengan Konsep Arsitektur Vernakular - Rian Aritama; Karya Subagya (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
Abstract Cultural tourism object is an area or region that is used as a container to preserve its cultural potential. Aside from being a container, cultural attractions also provide facilities for visitors to learn about the culture in the area This development plan seeks to provide a building function that facilitates cultural preservation and introduces culture in the area. The vernacular architectural theme that is applied aims to unite the climatic conditions in Indonesia with its application in its site and buildings. Keywords: Cultural Tourism Objects, Culture, Vernacular Architecture